Preparation and enhanced electrical properties of grain-oriented (Bi1/2Na1/2)TiO3-based lead-free incipient piezoceramics. Issue 9 (September 2015) - Zhang, Haibo; Xu, Peiwei; Patterson, Eric; Zang, Jiadong; Jiang, Shenling; Rödel, Jürgen
Abstract: (Bi1/2 Na1/2 )TiO3 (BNT) based lead-free incipient piezoceramics are promising candidates for actuator applications due to their giant electromechanical strains originating from the reversible relaxor-ferroelectric phase transition. To decrease the electric field required for this large strain, the templated grain growth method was employed to prepare 〈1 0 0〉 oriented 0.91Bi1/2 Na1/2 TiO3 –0.06BaTiO3 –0.03AgNbO3 piezoceramics using plate-like BNT templates. Textured samples provided a high unipolar strain of 0.38% and a corresponding large signal piezoelectric coefficient, d 33 ∗ of 766 pm/V at 5 kV/mm, which are 78% higher than the values of the randomly oriented ones. The enhanced electric-field-induced strain at relatively lower field was attributed primarily to the facilitated phase-transition to form a long range ferroelectric order along the 〈1 0 0〉 direction. It was also found that the textured piezoceramics exhibited significantly reduced frequency dependence in the unipolar strain behavior at room temperature, resulting from the decreased electric field required for the relaxor-ferroelectric phase transition.